Identifying a Novel DPYD Polymorphism Associated with Severe Toxicity to 5-FU Chemotherapy in a Saudi Patient. (21st August 2019) - Bukhari, Nedal; Azam, Faisal; Alfawaz, Mohammed; Zahrani, Mohammed
Abstract : Dihydropyrimidine dehydrogenase (DPD) is the major enzyme in the catabolism of 5-Fluorouracil (5-FU) and its prodrug capecitabine. We report a 65-year-old female with rectal adenocarcinoma who experienced severe toxicities secondary to standard dose 5-FU based chemotherapy. She was found to be heterozygous for rs371313778, c.2434G>A. This finding prompted restarting 5-FU at 50% dose reduction with further titration in subsequent cycles. We herein report the first case of rs371313778, c.2434G>A (p.Val812lle) DPYD polymorphism leading to severe 5-FU toxicities. The patient eventually completed a 6-month course of adjuvant treatment with modification of 5-FU dose.